Communicating social and environmental issues effectively - Reed, Betsy (United Kingdom : Emerald Publishing Limited, 2020)
This is the definitive guide to planning and delivering great communications on complex social and environmental issues. Including real-world case studies, practical exercises and clear frameworks, this book helps leaders, managers and marketing professionals plan, risk-proof and execute effective communications strategies.
Test Everything-Messages, Tactics and Channels, Assumptions -- Consider the Added Value of Allies, Advocates and Partnerships -- Step 3: Risk-Proof your Approach -- Step 4: Go Forth and Deliver -- In Summary -- Appendix 1-Further Resources -- A.1. General Resources on Communicating Social and Environmental Issues -- A.2. Building the Business Case -- A.3. Evaluation and Measurement -- A.4. Reader Enquiries -- Appendix 2-Tactical Planning Worksheet -- References -- Index.
Online resource; title from PDF title page (EBSCO, viewed July 29, 2020).
eBooks on EBSCOhost
Keywords: Communication in the environmental sciences; Communication in the social sciences; Environmental policy -- Social aspects; Communication en environnement; Environnement -- Politique gouvernementale -- Aspect social; Business communication & presentation; Business & Economics -- Business Communication -- General; Communication in the environmental sciences; Communication in the social sciences; Environmental policy -- Social aspects